Pengaruh Komunikasi Internal dan Budaya Organisasi Terhadap Kinerja Pegawai di Dinas Penanaman Modal dan Pelayanan Terpadu Satu Pintu (DPMPTSP) Provinsi Kalimantan Timur - Praditasari, Alvina Charisma; Nurfadillah, Mursidah; Fauziah, Fenty (Jurnal Ekonomika Dan Bisnis (JEBS), 2025)
The main problem in this study is the disharmony between employees, characterized by reluctance to share information or data with other colleagues, which causes internal communication to be less than optimal. In addition, there is a problem of organizational culture instability due to changes in leadership, causing employees to be confused in adapting to new work patterns and policies. This study aims to analyze and prove the influence of internal communication and organizational culture simultaneously on employee performance at the Investment and One-Stop Integrated Service Office (DPMPTSP) of East Kalimantan Province. This study uses quantitative research. The sampling technique uses non-probability sampling, namely saturated samples using the Slovin formula, obtained a sample of 65 respondents. Data collection was carried out using a questionnaire. Data analysis techniques in this study include validity testing, reliability testing, multiple linear regression analysis, classical assumption testing, and hypothesis testing with the help of the SPSS application. The results of the study show that (1) internal communication has a positive and significant effect on employee performance, (2) organizational culture has a positive and significant effect on employee performance, and (3) internal communication and organizational culture simultaneously have a positive and significant effect on employee performance at the Investment and One-Stop Integrated Services Agency (DPMPTSP) of East Kalimantan Province.